Molecular characterization and function analysis of the rice OsDUF946 family - Lihua Li; Taozhi Ye; Jinghong Xu; Chen Xie; Xiaoling Gao; Rongjun Chen; Jianqing Zhu; Zhengjun Xu (Biotechnology & Biotechnological Equipment, 2017)
The domain of unknown function DUF946 family consists of plant proteins with an average length of around 239 residues that have no characterized function. The gene family needs deeper characterization and functional analysis of its members. In this study, we report five OsDUF946 (OsDUF946.1–OsDUF946.5) family members in rice Nipponbare with three distinct motifs. All the OsDUF946 proteins were classified into three major groups (I, II, III) by phylogenetic analysis. Real-time polymerase chain reaction showed that the expression patterns of the five OsDUF946 family members were different in 15 different rice tissues as well as under various stress conditions and abscisic acid treatment. The expression of OsDUF946.1 was significantly downregulated under salt, cold and heat stress, while the expression of OsDUF946.4 and OsDUF946.5 was significantly upregulated under drought and salt conditions. Overexpression of OsDUF946.4 in Escherichia coli significantly improved the resistance to salt and drought, while overexpression of OsDUF946.5 in E. coli did not have such an effect. The obtained results provide a starting point for further research into the function of the OsDUF946 family in rice.